Persiapan ONMIPA-PT 2023 Bidang Matematika untuk Mahasiswa Perwakilan Universitas Muslim Indonesia - Syamsuddin Mas'ud (Jurusan Matematika FMIPA UNM, 2024)
Preparation of students to participate in the 2023 National Mathematics and Science Olympiad for Higher Education (ONMIPA-PT) in the field of mathematics is an effort to develop students' abilities in mathematics so they can compete with students from other universities under the Ministry of Education, Culture, Research, and Technology. This effort is specifically undertaken considering that the Universitas Muslim Indonesia does not yet have a mathematics program or similar, thus there are no students with sufficient mathematical foundations to participate in this competition. The preparation activity is attended by 5 student representatives and accompanied by a mentor. Mentorship involves explanations of the basics of mathematical subjects and providing practice problems to sharpen students' mathematical abilities. This preparation is conducted from May 15 to 24, 2023, in two stages. The first stage is held online via Zoom meetings and followed by the second stage offline at the Whiz Prime Hotel Sudirman Makassar. Through this preparation, students have gained new knowledge related to the mathematics topics competed in ONMIPA-PT such as combinatorics, linear algebra, and real analysis.